2019
DOI: 10.3390/molecules24162961
|View full text |Cite
|
Sign up to set email alerts
|

pH-Responsive Polypeptide-Based Smart Nano-Carriers for Theranostic Applications

Abstract: Smart nano-carriers have attained great significance in the biomedical field due to their versatile and interesting designs with different functionalities. The initial stages of the development of nanocarriers mainly focused on the guest loading efficiency, biocompatibility of the host and the circulation time. Later the requirements of less side effects with more efficacy arose by attributing targetability and stimuli-responsive characteristics to nano-carriers along with their bio- compatibility. Researchers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 215 publications
(229 reference statements)
0
21
0
Order By: Relevance
“…pH-triggered antibiotic release achieves increasing importance nowadays. Designing polymers with pH-responsive materials, for example poly-l-histidine [190], comes with the possibility of pH triggered surface charge switching in acidic medium of the infected bacteria. This specific feature is utilized to maximize the attraction force to the bacterial cell wall having negative charge and hence release the antibacterial drug more precisely in the targeted site.…”
Section: Smart Materialsmentioning
confidence: 99%
“…pH-triggered antibiotic release achieves increasing importance nowadays. Designing polymers with pH-responsive materials, for example poly-l-histidine [190], comes with the possibility of pH triggered surface charge switching in acidic medium of the infected bacteria. This specific feature is utilized to maximize the attraction force to the bacterial cell wall having negative charge and hence release the antibacterial drug more precisely in the targeted site.…”
Section: Smart Materialsmentioning
confidence: 99%
“…Several researches have reported that differences in pH between tumor and healthy tissue can be exploited to promote targeted anticancer therapy [ 12 ]. This has led to the exploration of different nanosized systems with pH-responsive properties for cancer treatment [ 13 ]. One example is the development of nanoparticles with a large structure to avoid blood clearance that shrink once pH decreases in tumor, enhancing cell penetration [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to vacuolar proton ATPase-mediated proton influx, the pH value of endosome and lysosome is lower than 6.0, NPs with ionizable groups (including amine, acyl sulfonamide, and imidazole) produce proton sponge effect to increase osmotic pressure in the inner compartment, eventually, realizing endosomal escape with the disruption of the plasma membrane. 69 , 70 Meanwhile, the low pH value of endo/lysosomal is the most widely used to achieve subcellular-targeted drug release by adding acid-sensitive bonds (such as hydrazone bonds) or protonated groups. However, acidic lysosome is common in normal cells not specific to tumor cells, so NPs triggered by lysosomes are needed to combine with other tumor cellular-specific stimuli to prevent off-target effects ( Figure 7 ).…”
Section: Msr-ddss Triggered By Combined Stimuli In Different Physiolomentioning
confidence: 99%
“… 71 Additionally, upregulated enzymes also serve as key stimuli for triggering signal turn-on with the significantly reduction of off-target effect owing to the high specificity of enzyme catalysis. 69 The cellular triggered reactions are designed in advance in the physical model, in which the macrostructures of the NPs changed by the over-expressed enzymes can result in a rapid release of payloads through transformation or degradation when the NPs reach the cytoplasm. 72 Among them, hydrolase and redox enzymes are more sensitive which are generally introduced to construct enzyme-triggered responsive NPs.…”
Section: Msr-ddss Triggered By Combined Stimuli In Different Physiolomentioning
confidence: 99%